Zihinsel yetersizliği olan bireylerde postür denge ve üst ekstremite fonksiyonelliğinin araştırılması - Emir, Ahmet (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2018)
Çalışmamızda amaç özel eğitim ve rehabilitasyon merkezlerinde eğitime devam eden Özel Öğrenme Güçlüğü (ÖÖG) ve Zihinsel Engelli (MR) tanılı çocuklarda postür, denge ve el kavrama kuvvetlerinin değerlendirilmesi ve ilişkilerinin incelenmesidir. Çalışmaya 6-18 yaş aralığında 36 ÖÖG, 21 MR tanılı çocuk ile 19 sağlıklı çocuk dahil edildi. Postür değerlendirmesi için "PostureScreen Mobile" uygulaması ile "New York Postür Analizi" kullanıldı. Denge değerlendirmesinde "Fizyosoft Balance System" kullanıldı. Denge değerlendirmesi gözler açık ve kapalı durumda statik olarak değerlendirildi. Elin kaba ve ince kavrama kuvvetleri her iki el için kilogram cinsinden değerlendirildi ve kaydedildi. Yaşam kalitesi değerlendirilmesi amacıyla "Pediatrik Yaşam Kalitesi Envanteri (PEDSQL)" uygulandı. Değerlendirmeler sonucunda postür değerlendirmesinde kontrol grubuna kıyasla iki grupta anlamlı farklılıklar gözlendi (p<0,05). Denge değerlendirmelerinde çocukların ağırlık merkezi değişimlerinde gruplar arası bazı parametrelerde anlamlı farklılıklar görüldü (p<0,05). Kavrama kuvvetleri her üç grupta da benzerdi (p>0,05). Yaşam kalitesinde kontrol grubuna göre hem ÖÖG hem de MR gruplarında anlamlı seviyede düşük skorlar görüldü (p<0,05). Postür değerlendirme parametreleri ile denge parametreleri arasında anlamlı ilişki bulundu (p<0,05). Yaşam kalitesi ile denge ve postür arasında anlamlı ilişki bulundu (p<0,05). Kavrama kuvvetleri ile baş postürü arasında anlamlı ilişki bulundu. Bu çalışma ÖÖG ve MR tanılı çocuklarda bilişsel yeteneklerin yanısıra motor beceri ve fiziksel etkilenim olabileceğini göstermiştir. Bu çocukların eğitim programlarına fizyoterapi eğitimlerinin de eklenmesi gerektiği görüşündeyiz.

The aim of our study is to assess the posture, balance and grip strength in children with Specific Learning Difficulties and Intellectual Disability who continue their therapy at special education and rehabilitation centers. 36 children with Specific Learnin Difficulties, 21 children with Intellectual Disability and 19 healthy children, ages ranging 6 to 18, were included in this study. In order to evaluate the posture, PostureScreen Mobile and New York Posture Analysis were applied. Fizyosoft Balance System is used to measure the balance and postural control. Balance assessment is done while subjects were stationary, and eyes both closed and open. Hand grabbing strength, both broad and fine were measured in kilograms for both hands and recorded. Pediatric Life Quality of Life Inventory (PEDSQL) is used to assess quality of life. After evaluations, significant differences were seen in posture assessment in contrast with the control group(p<0.05). While on balance evaluations, certain parameters in children's center of pressure change tests, showed interesting changes between groups(p<0.05). Grip strength was similiar in all three groups(p<0.05). Both children with Specific Learning Difficulties and Intellectual Disability had significant drop in quality of life assessment compared to the control group (p<0.05).. Assessments are reevaluated in relation to each other. A compelling correlation was found between posture assessment parameters and balance parameters(p<0.05). Another strong correlation was found between quality of life and balance and posture(p<0.05). Some sound correlation was also found between grip strength and head posture. In children diagnosed with Specific Learning Difficulties and Intellectual Disability, aside from cognitive skills, motor skills and biomecanichal structures are also affected. It is necessary to add a physiotherapy evaluation in regard to motor skills and posture to the training program, and if deemed necessary a physiotherapy program should also be added to the program.
Investigation of posture, balance and upper extremity functionality in individuals with intellectual impairment
Keywords: Özel Öğrenme Güçlüğü; Disleksi; Postür; Denge; Postural Kontrol; Zihinsel Yetersizlik; Specific Learning Disability; Dyslexia; Posture; Balance; Postural Control; Intellectual Disability